Implementing Linux on Integrated xSeries Solutions for iSeries - Ainsworth, Phil (IBM redbooks., 2004)
Integrated xSeries Solutions for iSeries deliver value to customers to reduce the cost and complexity of managing and deploying Windows Server applications on Intel. Support for Linux applications on Integrated xSeries Server or Integrated xSeries Adapter (IXS/IXA) is being offered to provide additional value to customers who require Linux applications to run on Intel servers, but who wish to leverage the powerful virtualization capabilities, shared resources, and operations of iSeries to support a Linux environment on xSeries servers. This IBM Redbooks publication will help you understand, plan, install, and configure Linux distributions on Integrated xSeries Server or Integrated xSeries Adapter.